Idiopathic intracranial hypertension in pregnancy: about a rare case - Elamouri, I.; Aissaoui, I.; Tahiri, H.; Saadi, H.; Mimouni, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
In this work, study report the case of a 23-year-old primigravidae, in whom an idiopathic intracranial hypertension (IIH), formerly called pseudotumor cerebri, was diagnosed in the first trimester with visual field impairment, the management of which was similar to cases of benign intracranial hypertension in the general population. The parturient put under medical treatment with ophthalmological and obstetrical follow-up until 39 weeks of amenorrhea where she was cesarized for rescue of the visual prognosis. The objective of this work is to elucidate this pathology, caused by a defect of reabsorption of the CSF by the arachnoid plexus. The diagnosis is retained after elimination by radio-biological exploration of an infectious, tumor or traumatic etiology. Idiopathic intracranial hypertension has no impact on the evolution of pregnancy. In addition, the choice of delivery route is dependent on the patient’s visual prognosis being brought into play.